2017
DOI: 10.1097/mib.0000000000001161
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Iron and Heme Iron Consumption, Genetic Susceptibility, and Risk of Crohnʼs Disease and Ulcerative Colitis

Abstract: Introduction Dietary iron and heme, likely through their effect on gut commensal bacteria and colonic barrier function, have been shown to modulate colonic inflammation in animal models of colitis. Nonetheless, the link between dietary total and heme iron and risk of Crohn’s disease (CD) and ulcerative colitis (UC) has not been previously explored. Methods We conducted a prospective cohort study of 165,331 U.S. women enrolled in the Nurses’ Health Study (NHS) and NHSII. Dietary information was collected usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
(40 reference statements)
0
33
0
Order By: Relevance
“…Early work from the NHS and NHSII showed a low risk of Crohn’s disease among individuals who consume high amounts of fiber, particularly fiber from vegetables and fruits (Table 1) 40 . By contrast, a high n-3:n-6 fatty acids ratio was associated with a low risk of ulcerative colitis, whereas a high intake of red meat was associated with an increased risk of ulcerative colitis (Table 1) 41, 42 . Owing to the increasingly recognized role of specific nutrients and electrolytes such as heme, potassium and zinc in regulating the intestinal barrier and immune function 4350 , over the past 5 years studies have focused on examining the relationship between quantity of nutrient consumption and risk of IBD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early work from the NHS and NHSII showed a low risk of Crohn’s disease among individuals who consume high amounts of fiber, particularly fiber from vegetables and fruits (Table 1) 40 . By contrast, a high n-3:n-6 fatty acids ratio was associated with a low risk of ulcerative colitis, whereas a high intake of red meat was associated with an increased risk of ulcerative colitis (Table 1) 41, 42 . Owing to the increasingly recognized role of specific nutrients and electrolytes such as heme, potassium and zinc in regulating the intestinal barrier and immune function 4350 , over the past 5 years studies have focused on examining the relationship between quantity of nutrient consumption and risk of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the increasingly recognized role of specific nutrients and electrolytes such as heme, potassium and zinc in regulating the intestinal barrier and immune function 4350 , over the past 5 years studies have focused on examining the relationship between quantity of nutrient consumption and risk of IBD. Preliminary data from these cohorts have shown an inverse association between dietary zinc and potassium intake and risk of Crohn’s disease, whereas dietary sodium, heme and iron intake were not associated with IBD risk (Table 1) 42, 51, 52 .…”
Section: Introductionmentioning
confidence: 99%
“…48 However, contrary to our findings, epidemiologic studies have mostly demonstrated an association between red meat intake and UC. 49 In addition, patients with CD have an abnormal expression of carcinoembryonic antigen-related cell adhesion molecule 6, a receptor for adherent-invasive Escherichia coli, in the ileal epithelium. 50 Martinez-Medina et al 29 showed that a diet high in fat and sugar alters the composition of intestinal microbiota and host homeostasis (eg, increased intestinal permeability and TNF-a secretion) in carcinoembryonic antigen-related cell adhesion molecule 10 transgenic mice, leading to a higher ability of adherent-invasive E. coli to colonize the gut mucosa and induce inflammation.…”
mentioning
confidence: 99%
“…In the USA, a prospective cohort study showed no significant association between dietary heme iron consumption and the risk of UC. The study concluded that dietary heme iron and the risk of UC may be modified by a variant in genetic susceptibility to UC …”
Section: Discussionmentioning
confidence: 99%